1 - Theorising the Intersection of Public Policy and Personal Lives through the Lens of ‘Participation’ - Anyidoho, Nana Akua (Africa Development, 2021)
The continued interest in political economy-inspired perspectives on economic and social policies is an attempt to understand policymakers as human beings who are influenced by values, votes and other factors that were once thought to be exogenous to policy choices. However, there is still little theorising about those on the other side of the policy equation. This article seeks a better understanding of how ordinary people engage in a very personal way with policy. I present a model of participation grounded in empirical research with members of a poverty-reduction project in Ghana, and a conceptual framework informed by an interpretive or sense-making approach to policy analysis. The model is based on the three principles of ‘subjectivity’, ‘temporality’ and ‘situatedness’: First, human beings make subjective interpretations of policy grounded in their life histories; secondly, temporality is an inherent aspect of how individuals cognitively organise their lives; and thirdly, people experience policy as one of many overlapping contexts in which they are situated.